The Effect of Lego Games on Improving Children’s Creativity Development - Id'ha Tutfi Ulkhatiata; Purnama, Sigit (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2022)
Purpose – This study aims to determine the effect of the lego game on lego games in increasing the development of creativity in children aged 4-5 years at TK Aisyiyah ABA Konang Glagah Lamongan. Following the problems found in the field, the lack of learning the media used by teachers results in children feeling bored more quickly in carrying out teaching and learning activities and only emphasizing their academic development so that the development of creativity is not given enough attention.Design/methods/approach – This type of research uses a quantitative approach with a pre-experimental type and a one-group pretest-posttest design in collecting the data, namely making initial observations before being given treatment, treatment, and final observations after being given treatment. Data collection techniques used observation and documentation; data analysis used IBM SPSS with paired samples t-test. In this research, researchers conducted data mining using research instruments on children aged 4-5 years in TK Aisyiyah ABA Konang Glagah Lamongan.Findings – The results of the study show that the influence of the use of lego games increases the development of children’s creativity—the output of the paired sample t-test evidence this A significant value is obtained, namely 0.008 < 0.05. It indicates that H0 is rejected and Ha is accepted, meaning that there is a significant influence on increasing the development of children’s creativity using lego games.Research implications/limitations – This research only focuses on children aged 4-5 years with a limited number of 15 whose area is only in TK Aisyiyah ABA Konang Glagah Lamongan and in this study only uses lego games as a medium to increase the development of creativity in children.Practical implications – The results of this study are expected to help parents understand the creative talents possessed by children so that they can stimulate this development with the right strategies and methods.Originality/value – This research provides an in-depth understanding of one of the early childhood learning media to enhance creativity development using lego game media.Paper type: Research paper